2017
DOI: 10.14202/vetworld.2017.1464-1470
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on seroprevalence of bluetongue virus in Haryana state of India

Abstract: Aim:The aim of present study was to determine seroprevalence of bluetongue virus (BTV) in Haryana state of India.Materials and Methods:A total of 803 serum samples, 408 of cattle and 395 of buffalo origin, respectively, were collected from different villages of Haryana. Sampling was done randomly to obtain unbiased results. The samples were evaluated by a competitive enzyme-linked immunosorbent assay for the presence of BTV antibodies.Results:Overall seroprevalence of BTV antibody in cattle and buffaloes for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
9
0
2
Order By: Relevance
“…BTV seroprevalence of varying percentages was reported by several authors before [11][12][13][14][15][16][17]. In BT endemic countries such as India, high seroprevalence (>50%) is usually reported [18][19][20][21][22]. Especially, in the tested region included in the present study, the previous studies reported 61% seroprevalence of BTV during 2005-2009 and 75% during 2014-2017 [5,23,24].…”
Section: Discussionsupporting
confidence: 48%
“…BTV seroprevalence of varying percentages was reported by several authors before [11][12][13][14][15][16][17]. In BT endemic countries such as India, high seroprevalence (>50%) is usually reported [18][19][20][21][22]. Especially, in the tested region included in the present study, the previous studies reported 61% seroprevalence of BTV during 2005-2009 and 75% during 2014-2017 [5,23,24].…”
Section: Discussionsupporting
confidence: 48%
“…Serological data show that twenty-two BTV serotypes exist in India, making it a region with one of the highest levels of BTV diversity in the world (Rao et al. 2016; Maan et al. 2017).…”
Section: Introductionmentioning
confidence: 99%
“…10, 14, 16, 30, 40), and one each in cattle (study no 21) and buffaloes (study no 9). Among the studies which contributed to overall heterogeneity, one study each in sheep (study no 37, Doddamani and HariBabu 2006 ) and in buffaloes (study no 9, Maan et al 2017 ) was identified as an influential study. The sensitivity analysis after removing the influential studies revealed that the seroprevalence was marginally increased in sheep from 44% to 46% while decreased from 34% to 31% in buffaloes.…”
Section: Resultsmentioning
confidence: 99%
“…Even though AGID was a prescribed test for international trade, it lacks sensitivity, specificity and cross reacts with other Orbivirus serogroups, (Hamblin 2004 ). The serological response in BTV infection usually appears 7–14 days’ post-infection, and the antibodies can persist between 2 weeks and 6 years after infection (Eschbaumer et al 2012 ; Maan et al 2017 ). In common, BT seroprevalence in different animals is done either using AGID assay or c-ELISA (OIE 2012).…”
Section: Discussionmentioning
confidence: 99%